Upaya Meningkatkan Aktivitas Dan Keterampilan Proses Sains Melalui Metode Eksperimen - Adam Ilham Ardliansyah (Jurnal Ilmu Pendidikan Biologi dan IPA, 2026)
This study aimed to improve students’ learning activities and science process skills through the implementation of the experimental method in science learning. The research employed a classroom action research (CAR) approach conducted in two cycles, consisting of planning, action, observation, and reflection stages. The research subjects were students of class ___ at a selected school. Data were collected through observations of learning activities, science process skills tests, and documentation. The data were analyzed using descriptive quantitative and qualitative methods. The results indicated that the experimental method effectively increased students’ learning activities from a moderate to a good category. In addition, students’ science process skills showed a significant improvement in each cycle. Therefore, it can be concluded that the experimental method is effective in enhancing students’ learning activities and science process skills in science learning.